THE IMPACT OF PERCEIVED USEFULNESS, PERCEIVED EASE-OF-USE AND PERCEIVED VALUE ON USER’S INTENTION TO CONTINUE USING SHOPEEPAY - Precillia Hartono; Joy Tulung; Ferdinand Tumewu (Universitas Sam Ratulangi, 2023)
The purpose of this study was to determine the effect of Perceived Usefulness, Perceived Ease-of-Use, and Perceived Value on User’s Intention to Continue using ShopeePay. Data analysis methods used is Multiple Regression Analysis. The sample in this research are young consumers in Manado who have used the ShopeePay. For this reason, this research requires around 100 Respondents. Sampling in this study is to use the Non-Probability Sampling technique by Purposive Sampling. The results are (1) Perceived Usefulness affects ShopeePay User Continuance Intention among young consumers in Manado. (2) Perceived Ease-of-Use affects ShopeePay User Continuance Intention among young consumers in Manado. (3) Perceived Value affects ShopeePay User Continuance Intention among young consumers in Manado, and (4) Simultaneously, Perceived Usefulness, Perceived Ease- of-Use and Perceived Value affects ShopeePay User Continuance Intention among young consumers in Manado. Keyword: perceived usefulness, perceived ease-of-use, perceived value, user’s intention to continue